Kaisertum und Kaiserkult: Ein Vergleich zwischen Philos Legatio ad Gaium und der Offenbarung des Johannes - Gradl, Hans-Georg 1973- (2010)
In face of the religious and cultic claims of the Roman emperors, Philo (Legatio ad Gaium) and Revelation develop contrasting perspectives in positioning their respective religious communities within the cultural majority of their day. The Alexandrian Jew Philo opts for critical integration and social cohabitation—a solution that is conventionally ascribed to early Christianity. John pleads strongly for the self-isolation of the Christian minority groups in the Province of Asia—a solution conventionally ascribed to Jewish self-definition in the Tannaitic period. The article illustrates this remarkable exchange of religious and social self-conceptualisations in both authors. Social rather than religious boundaries determine the framework in which the Roman Empire and its ruler are conceptualised, literary reactions are developed, and strategic alternatives are formed.
Keywords: Philo; Minorities; Criticism of Power; imperial cult; Caligula; Apocalypse of John